2020
DOI: 10.1111/jvim.15740
|View full text |Cite
|
Sign up to set email alerts
|

Dental disease in alpacas. Part 2: Risk factors associated with diastemata, periodontitis, occlusal pulp exposure, wear abnormalities, and malpositioned teeth

Abstract: Background Dental disorders, of which tooth root abscesses are best documented, are highly prevalent in alpacas. Identification of risk factors can be valuable for prevention of dental disorders in this species. Hypothesis/Objectives To identify risk factors associated with wear abnormalities, malpositioning, diastemata, periodontal disease (PD), and occlusal pulp exposure at the level of the cheek teeth. Animals Two hundred twenty‐eight alpacas (Vicugna pacos) from 25 farms. Methods Cross‐sectional study. Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(66 reference statements)
1
12
0
Order By: Relevance
“…A more concave line would be interpreted as a lower BCS, a more convex line as a higher BCS [ 15 , 16 ]. Causes for a bad nutritional status in SAC include management problems such as a restricted animal/feeding place ratio, insufficient nutrient supply, infestation with endoparasites, tooth problems, or any other chronical disease [ 4 , 17 , 18 , 19 ]. To date, there are several descriptions about the assessment of BCS in SAC, and there is also some information available about the relationship between BCS and health in llamas and alpacas [ 11 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A more concave line would be interpreted as a lower BCS, a more convex line as a higher BCS [ 15 , 16 ]. Causes for a bad nutritional status in SAC include management problems such as a restricted animal/feeding place ratio, insufficient nutrient supply, infestation with endoparasites, tooth problems, or any other chronical disease [ 4 , 17 , 18 , 19 ]. To date, there are several descriptions about the assessment of BCS in SAC, and there is also some information available about the relationship between BCS and health in llamas and alpacas [ 11 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Causes for a bad nutritional status in SAC include management problems such as a restricted animal/feeding place ratio, insufficient nutrient supply, infestation with endoparasites, tooth problems, or any other chronical disease [ 4 , 17 , 18 , 19 ]. To date, there are several descriptions about the assessment of BCS in SAC, and there is also some information available about the relationship between BCS and health in llamas and alpacas [ 11 , 19 , 20 ]. However, so far, there is a lack of data concerning the BCS of SAC presented in the veterinary clinic.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding outside of South America is generally richer and doesn’t include a lean time, thereby predisposing the animals to become obese. Furthermore, the use of different feedstuffs and differing management conditions might predispose alpacas to the development of specific dental disorders, as is also perceived in domesticated horses [ 5 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tooth root abscesses, also termed apical infections, have received great attention in specific veterinary literature [ 1 3 ]. Recent studies have attributed to novel insights into the prevalence of specific dental disorders in alpacas [ 4 , 5 ]. Several wear abnormalities at the level of the cheek teeth, including step mouth, wave mouth, enamel overgrowths, focal overgrowths and accentuated transverse ridges have been proven to be of importance in this species [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The early, specific veterinary literature on dental disease in camelids mainly focused on tooth root abscesses [ 1 3 ]. Recent studies have shown a high prevalence of other dental problems that are believed to precede tooth root abscesses, indicating that dental disease in general remains underdiagnosed in this species [ 3 , 4 ]. A lack of sufficient in-depth scientific knowledge with regards to normal anatomy and physiology of alpaca cheek teeth hinders proper understanding of the pathogenesis of specific dental problems [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%